RP-HPLC Determination of Aripiprazole in Pharmaceutical Formulations - SASTRY, B.S.; GANANADHAMU, S.; DEVALA RAO, G. (Asian Journal of Chemistry, 2010)
A rapid, sensitive and specific reverse phase-high performance liquid chromatography (RP-HPLC) method was developed for the estimation of aripiprazole in pharmaceutical formulations. The RP-HPLC analysis was performed isocratically on a Phenomenex Luna C18 column (250 mm length, 4.6 mm internal diameter and 5 μm particle size) using mobile phase having a composition of acetonitrile and sodium acetate buffer (20 mM sodium acetate, pH adjusted to 4.50 with acetic acid after addition of 0.4 % triethyl amine) in 55:45 v/v proportion with a flow rate of 1.0 mL/min. The analyte was monitored with UV detector at 254 nm. In the developed method aripiprazole elutes at a typical retention time of 6.84 min. The proposed method is having linearity in the concentration ranging from 2-12 μg/mL of aripiprazole. The method was statistically validated and had been applied to analysis of the drug in tablet dosage forms.